2005
DOI: 10.2202/1556-3758.1016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Physico-Chemical Characteristics of Dried Meat Processed by Different Methods

Abstract: Thirty longissimus dorsi (LD) muscles from Omani male goats were dried by five methods (sun, air, vacuum, freeze and modified atmosphere drying). Dried strips from the longissimus dorsi samples were evaluated for microbial, chemical and fatty acid composition and physical quality (pH, expressed juice, rehydration ratio, and color L*, a* and b* values). The method of drying had a significant effect on the microbial counts, pH, volume of expressed juice, color, rehydration ratio, and fatty acids content of LD sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…Different drying methods, packaging techniques, storage temperatures have significant influence on the pH of the dehydrated meat products. Air dried meat products show higher pH value than freeze dried meat products (Rahman et al, 2005). The difference in pH values is due to loss of free acidic groups depending on drying procedures (Nayar et al, 2014).…”
Section: Physico-chemical Characteristics Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Different drying methods, packaging techniques, storage temperatures have significant influence on the pH of the dehydrated meat products. Air dried meat products show higher pH value than freeze dried meat products (Rahman et al, 2005). The difference in pH values is due to loss of free acidic groups depending on drying procedures (Nayar et al, 2014).…”
Section: Physico-chemical Characteristics Phmentioning
confidence: 99%
“…Drying techniques have significant role in the development of porosity in the meat samples. Higher the porosity in meat structure, higher will be the rehydration ration in the dried meat product (Rahman et al, 2005). Rehydration depends on the water absorption capacity, water holding capacity of muscle fibres and the formation of spaces within muscle fibres, affecting dehydration, …”
Section: Page15mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this investigation did not specify any result regarding water activity, nor it reported water holding capacity changes of the studied muscles. Rahman et al [16] conducted an investigation of the physical-chemical properties of jerky using goat meat and different drying methods. They concluded that drying methods affect quality attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of meat and meat products is an integral component of the human diet (Reddy, Hurrell, & Cook, 2006), especially since these commodities not only prove to be appealing to the palate, but are also high sources of amino acids and B-complex vitamins and minerals (Friedman, 1996;Jimenez-Colmenero, Carballo, & Cofrades, 2001;Rahman et al, 2005). Historically, fresh meats have gained a reputation for being highly perishable commodities (Lee & Fung, 1986;Mothershaw, Rahman, Mohamad, & Guizani, 2003;Poligne, Colligan, & Trystram, 2005).…”
Section: Introductionmentioning
confidence: 99%